Peranan Komunikasi Antar Pribadi Orang Tua Dengan Anak Dalam Meningkatkan Prestasi Belajar Di Kelas VI Pada SD Negeri BTN Pemda Kota Makassar - kadariah, kadariah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This study aims to describe the role of communication between parents and children in improving student achievement in Class VI at SDN BTN Pemda of Makassar City. The approach used is collaboration between qualitative approaches and quantitative approaches. This type of research is classroom action research. To obtain data and information needed, tests, documentation and observations are used. For the purposes of managing data in this study, descriptive analysis is used. The results of the study showed that there was a significant relationship between interpersonal communication between parents and children with the learning achievements of class VI students. This is evidenced by the research data calculated using the product moment correlation formula with the help of SPSS 16. The results of the study show that: (1) there is a significant positive relationship between parent and child interpersonal communication with student achievement. (2) The magnitude of the communication relationship between parents and children towards student achievement is classified as very strong